(untitled) (International Journal of Engineering and Computer Science, 2013)
One of the main success factors on which the grid computing depends is how quickly and correctly a computer is able to locate the resources like memory, CPU etc. in the Grid. With the increase in the size of grid, this search can take a considerable amount of time which could degrade the application performance. In this paper we present a middleware Grid component, Grid Resource Software (GRS) that can be used by the end user system to identify the resources in lesser time.